Enhanced high-sensitivity multi-layer neutron detector based on LiF:ZnS(Ag) scintillator - Ilan Cohen Zada; Alon Osovizky; Itzhak Orion (Scientific Reports)
Abstract This study proposes a novel, highly sensitive neutron detector design utilizing a unique multi-layered configuration. Each layer consists of a LiF: ZnS(Ag) scintillator coupled with a transparent neutron moderator that also functions as a light guide for the Silicon Photomultiplier (SiPM) light sensor. This design offers a cost-effective and readily available alternative for existing neutron detectors. The research focused on optimizing a single layer for maximum sensitivity and proper gamma rejection capabilities. This optimized configuration is then replicated to form the multi-layer detector. A primary challenge with the LiF:ZnS(Ag) scintillator is its inherent opacity, limiting its width and consequently, its detection efficiency. Our proposed multi-layer structure addresses this limitation by employing a thin scintillator in each layer. This strategic design minimizes emitted light attenuation while simultaneously enhancing sensitivity through the cumulative effect of multiple layers. Our experiments demonstrate a significant improvement in detection efficiency compared to the single-layer setup. Additionally, our architecture offers an actual improvement in differentiating between gamma and neutron signals. By analyzing count rates across the detector’s layers, we gain valuable operational insights, such as the ability to predict the source direction. Our finding demonstrates an improved sensitivity achieved by minimal loss of neutrons during the moderation of 329% compared to a single layer, aligned with the potential range of improvement while maintaining extremely high gamma rejection. Supported by the presented findings, this design represents a noticeable advancement over existing solutions, offering scalable customization to user requirements. Notably, it outperforms traditional 3He tube-based detection configurations, positioning it as a compelling and advantageous replacement option.